Development Of Module Based On Malay Culture As A Learning Resource Students In Tanjung Pura City - Nurjehan, Rizki; Sinaga, Bornok (JURNAL BUNGA RAMPAI USIA EMAS, 2017)
The research is a development research with the aim to produce a product in the form of Malay Culture based module as a valid and effective learning resource. This research is done through development stage which refers to Thiagarajan, Semmel and Semmel development design that is 4-D design (four D models). The findings of the research are: 1) the developed module product meets the criteria of good / valid; 2) the effectiveness of the module is summarized based on: (i) Student learning completeness classically in the first test of 79.41% and in the second test of 82.35%, (ii) the achievement of the student's active activity and the ideal time on trial I and trial II is ideal; iii) students' positive responses to module product development on trial I of 92.65% and 95.92% in second try, and (iv) teacher management in learning on trial I and II is good.